An Analysis of Preserving Imaginative and Mythological Elements in Indonesian Lyrics Translation - Miftahul Hidayatulloh; Syamsurrijal Syamsurrijal; Muhammad Zaki Pahrul Hadi (JALILA: Journal of Applied Linguistics and Literary Analysis, 2025)
This study investigates the preservation of imaginative and mythological components in the Indonesian translation of J.R.R. Tolkien's "Far Over the Misty Mountains Cold." The words are abundant in fantastical places, mythical figures, and vibrant natural imagery that establish an enchanting ambiance. Translating such a text necessitates meticulous attention to preserve symbolic significance, aesthetic elegance, and cultural subtleties. This research employs a descriptive qualitative methodology utilizing comparative text analysis between the source and target texts. The results indicate that although the translation effectively preserves mythical names and the fundamental narrative structure, essential poetic elements like melody, rhyme, and metaphorical richness are often diminished. This influences the interpretive depth and the poetic ambiance of the original. The study emphasizes that while the fundamental content is retained, the preservation of poetic aesthetics is a significant challenge. It suggests further solutions including footnotes, adaptable rhythmic variations, and innovative methods to maintain the imaginative and symbolic dimensions for the intended audience.